Acupuncture – Basic Research and Clinical Application - Gerhard Litscher (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book focuses on the investigation, development, and modernization of acupuncture in basic research settings as well as in clinical applications. The book contains 13 chapters reporting the latest evidence-based results of acupuncture research and exploring acupuncture in general. Altogether, 44 authors from all over the world contributed to this book.